Totipotency in the mouse - Wu, Guangming (J Mol Med (Berl), 2017)
In mammals, the unicellular zygote starts the process of embryogenesis and differentiates into all types of somatic cells, including both fetal and extraembryonic lineages—in a highly organized manner to eventually give rise to an entire multicellular organism comprising more than 200 different tissue types. This feature is referred to as totipotency. Upon fertilization, oocyte maternal factors epigenetically reprogram the genomes of the terminally differentiated oocyte and spermatozoon and turn the zygote into a totipotent cell. Today, we still do not fully understand the molecular properties of totipotency. In this review, we discuss recent findings on the molecular signature and mechanism of transcriptional regulation networks in the totipotent mouse embryo.